Proteomics-Based Retinal Target Engagement Analysis and Retina-Targeted Delivery of 17β-Estradiol by the DHED Prodrug for Ocular Neurotherapy in Males - Katalin Prokai-Tatrai; Khadiza Zaman; Vien Nguyen; Daniel L. De La Cruz; Laszlo Prokai (MDPI AG, 2021)
We examined the impact of 17β-estradiol (E2) eye drops on the modulation of the proteome profile in the male rat retina. With discovery-driven proteomics, we have identified proteins that were regulated by our treatment. These proteins were assembled to several bioinformatics-based networks implicating E2's beneficial effects on the male rat retina in a broad context of ocular neuroprotection including the maintenance of retinal homeostasis, facilitation of efficient disposal of damaged proteins, and mitochondrial respiratory chain biogenesis. We have also shown for the first time that the hormone's beneficial effects on the male retina can be constrained to this target site by treatment with the bioprecursor prodrug, DHED. A large concentration of E2 was produced after DHED eye drops not only in male rat retinae but also in those of rabbits. However, DHED treatment did not increase circulating E2 levels, thereby ensuring therapeutic safety in males. Targeted proteomics focusing on selected biomarkers of E2's target engagement further confirmed the prodrug's metabolism to E2 in the male retina and indicated that the retinal impact of DHED treatment was identical to that of the direct E2 treatment. Altogether, our study shows the potential of topical DHED therapy for an efficacious and safe protection of the male retina without the unwanted hormonal side-effects associated with current estrogen therapies.